PENGARUH EARNING PER SHARE, DEBT EQUITY RATIO, PRICE EARNING RATIO TERHADAP RETURN SAHAM - Teni Eriyanti; Dwi Urip Wardoyo; Nanda Annisa Putri; Juwita Nur Hassanah; Lidiya Aprilia (Pusat Riset dan Inovasi Nasional, 2023)
Investment in a company is very important so that the company can carry out its business activities. Companies with a high level of investment will be able to attract investors who have an effect on stock returns or profits to be obtained by investors. The object of this study is to examine the Customer Goods sub-sector companies listed on the IDX. This study aims to determine the effect of earnings per share (EPS) on stock returns, the effect of debt-equity ratio (DER) on stock returns, and the effect of price-earnings ratio (PER) on stock returns. The method used in this study is a quantitative method with secondary data. This study's population consisted of all consumer goods companies listed on the IDX from 2018 to 2021.The sample was taken using a purposive sampling technique. The analysis technique used in this study uses multiple linear regression techniques using the classical assumption test (F), multicollinear test, and t test. The results of this study indicate that EPS does not have a significant negative effect on stock returns. DER has no significant effect on stock return, so H2 is rejected. H1 is rejected because PER has no partially significant effect on stock return.